Efektivitas Kombinasi Daun Gamal (Gliricidia sepium) dan Buah Bintaro (Cerbera manghas) sebagai Insektisida Alami terhadap Tanaman Terong (Solanum melongena) - Hotimah, Auliya Khusnul; Nasution, Ruqoyyah; Jailani, Jailani; Serena, Nelda Anasthasia (Biocaster : Jurnal Kajian Biologi, 2025)
The excessive use of chemical pesticides has a negative impact on the environment and health, so a more environmentally friendly pest control alternative is needed. This study aims to determine the effectiveness of the combination of gamal leaf extract (Gliricidia sepium) and bintaro fruit (Cerbera manghas) as a vegetable insecticide against pests in eggplant (Solanum melongena). The research method used pure experiments with a Complete Random Design (RAL) of five concentration treatments, namely 0% (control), 10%, 30%, 50%, and 70%. The observation data was analyzed using the ANOVA test. The results showed that the combination of gamal leaf extract and bintaro fruit had a significant effect in suppressing pest populations in eggplant plants, with a Fcal value of 11.750 and a significance value of 0.000 (< 0.05). The 70% concentration is the most effective treatment in reducing the intensity of pest attacks compared to other treatments and controls. This success is supported by the content of bioactive compounds, such as flavonoids, saponins, alkaloids, and cerberins that act as contact poisons and stomach toxins in the target insects. These findings suggest that the combination of the two extracts could be a safe, economical, and sustainable alternative to plant insecticides to support the cultivation of horticultural crops without relying on synthetic chemical pesticides.